A synthesis of soil carbon and nitrogen recovery after wetland restoration and creation in the United States - Lingfei Yu; Yao Huang; Feifei Sun; Wenjuan Sun (Scientific Reports, 2017)
Abstract Wetland restoration and creation efforts have been widely attempted as a way to compensate for wetland losses and to recover wetland functions; however, to date, there has been no comprehensive evaluation of the efficacy of soil carbon (C) and nitrogen (N) content recovery at a regional scale. This meta-analysis synthesizes 48 articles to identify the general patterns of soil C and N change after wetland restoration and creation in the United States. Our results indicate that, after 11–20 years, soil C and N in restored and created wetlands are still significantly lower by 51.7% and 50.3%, respectively, than those in natural wetlands. The soil C and N in restored wetlands recovered faster than in created wetlands. Furthermore, the soil C in restored organic flat and created depressional wetlands recovered more rapidly than in restored and created hydrologically open wetlands (riverine and tidal), respectively. Mean annual temperature and soil texture were recognized as two crucial abiotic factors affecting soil C and N recovery. Linear regression analysis revealed a positive relationship between the restoration and creation effect sizes on soil C and N, indicating that wetlands may alleviate N limitations intrinsically during C recovery processes.